2019
DOI: 10.1002/btpr.2774
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and scale up of itaconic acid production from potato starch waste in stirred tank bioreactor

Abstract: Present study used Aspergillus terreus strain C1 isolated from mangrove soil for itaconic acid (IA) production from potato starch waste. Fermentation parameters were optimized by classical one factor approach and statistical experimental designs, such as Plackett-Burman and response surface designs. Anionic deionization of potato waste was found to be a very effective, economic, and easy way of improving IA production. The increase in IA production by deionization was found to correlate with removal of phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to a study based upon fermentation of starch-rich industrial wastes (rice, potato, corn), the maximum itaconic yield was obtained with potato starch waste. Further deionization of potato starch led to enhanced yield (Bafana et al, 2019(Bafana et al, , 2017. In another study, 31 and 28.5 g/L itaconic acid was obtained through fermentation of α-amylase and nitric acid hydrolysate of corn starch, respectively, using A.…”
Section: Aspergillus Strainsmentioning
confidence: 99%
“…According to a study based upon fermentation of starch-rich industrial wastes (rice, potato, corn), the maximum itaconic yield was obtained with potato starch waste. Further deionization of potato starch led to enhanced yield (Bafana et al, 2019(Bafana et al, , 2017. In another study, 31 and 28.5 g/L itaconic acid was obtained through fermentation of α-amylase and nitric acid hydrolysate of corn starch, respectively, using A.…”
Section: Aspergillus Strainsmentioning
confidence: 99%
“…Smerilli et al () indicated that potato residues could be an attractive raw material in the lactic acid production, since they offer large amount of starch as a C‐source as well as supplementary nutrients for microbial growth. Bafana et al () also optimised and scaled up the itaconic acid production from potato starch wastes with suitable results. Raigond et al () studied the possibility of converting starch from waste potatoes and peel wastes in high valuable nanocrystals, which can be further modified as desired.…”
Section: Components In Potato Wastes: Composition and Propertiesmentioning
confidence: 99%